Balancing quietness and freedom: Support for reducing road noise among park visitors. (March 2022) - Rice, William L.; Newman, Peter; Zipp, Katherine Y.; Taff, B. Derrick; Pipkin, Ashley R.; Miller, Zachary D.; Pan, Bing
Abstract: The importance of natural soundscapes and natural quiet to the recreational experience in protected areas is well established. While a growing body of research examines how recreationists are impacted by anthropogenic noise that inhibits their experience of natural soundscapes, a very limited amount of research examines recreationists' preferences for soundscape management. In fact, sparse research examines park visitors' preferences concerning the management of road noise—perhaps the greatest source of noise pollution in protected areas. It is therefore the purpose of this study to bridge a significant gap in the protected area soundscape literature by examining how varying road noise management actions—including quiet pavement—impact recreationist utility. In this research, the results of a field-based choice experiment in Death Valley National Park (USA) are used to analyze how visitors navigate the tradeoff between natural quiet and freedom and how varying management actions impact recreationist utility. Results show that recreationists require substantial gains in quietness to relinquish freedom; and quiet pavement and reduced speed limits have the least negative impact on recreationist utility. Implications of these results include improved management of road noise in protected areas and considerations for future research of park soundscapes. Management implications: This research highlights the important roles natural quiet and freedom play in hikers' experiences in parks and protected areas. In this case of road noise mitigation, quiet pavement and reduced speed limits represent management actions that can achieve reduced road noise while remaining relatively unobtrusive to the recreationist experience and not leading to substantial losses in freedom. However, park managers must also consider the demographics and noise sensitivity of their visitors when assessing their soundscape management options, as the impacts of management actions and noise dispersion vary across nationality and noise sensitivities.